Multiplexed amplicon sequencing reveals the heterogeneous spatial distribution of pyrethroid resistance mutations in Aedes albopictus mosquito populations in southern France - Albin Fontaine; Antoine Mignotte; Guillaume Lacour; Agnès Nguyen; Nicolas Gomez; Lionel Chanaud; Grégory L’Ambert; Sébastien Briolant (Parasites & Vectors)
Abstract Background The risk of mosquito-borne disease transmission is increasing in temperate climates with the colonization and proliferation of the Asian tiger mosquito vector Aedes albopictus and the rapid mass transport of passengers returning from tropical regions where viruses are endemic. The prevention of major Aedes-borne viruses heavily relies on the use of insecticides for vector control, mainly pyrethroids. In Europe, only deltamethrin is authorized. Methods High-throughput molecular assays can provide a cost-effective surrogate to phenotypic insecticide resistance assays when mutations have been previously linked to a resistance phenotype. Here, we screened for the spatial distribution of knockdown resistance (kdr) mutations at a large scale using a two-step approach based on multiplexed amplicon sequencing and an unprecedented collection of field-derived mosquitoes from 95 sites in 61 municipalities, alongside a west-to-east transect in the south of France, from June to September 2021. Results We identified the presence of the V1016G allele in 14 sites. The V1016G allele was predominantly found in southeast France close to the Italian border, with two additional isolated sites close to Bordeaux and Marmande. All mosquitoes were heterozygous for this mutation and should not be phenotypically resistant to pyrethroid insecticide. Four other mutations were identified in our targeted genomic sequence: I1532T, M1006L, M1586L, M995L. Sequencing a section of maternally inherited mitochondrial genome confirmed that the spread of Ae. albopictus in France originated from founders within haplogroup A1. Conclusions These findings contribute to the broader understanding of resistance dynamics in Europe and can inform targeted approaches to mitigate the impact of resistance on vector control.